Low-Cost Early Detection Device for Breast Cancer based on Skin Surface Temperature - Arsyad Cahya Subrata; Sirajuddin, Muhammad Mar’ie; Salsabila, Sona Regina; Ibad, Irsyadul; Prasetyo, Eko; Yusmianto, Ferry (IT Journal Research and Development, 2024)
One of the deadly diseases that attacks many women is breast cancer. It was recorded that breast cancer cases in 2020 were 2.3 million, with deaths accounting for 29% of these cases. The BSE technique is an easy way of early identification of breast cancer that can be done independently. However, this technique often goes wrong when practiced, making it ineffective. An early breast cancer detection system is proposed to make it easier for women to carry out early identification independently. Detection is carried out based on the measured temperature of the breast surface. The temperature difference at each point is a reference for the potential for breast cancer. This system was built in a bra and tested with a mannequin as a simulator subject. The MLX90614 temperature sensor, as the primary sensor, succeeded in measuring the surface temperature of the dummy with 99% accuracy. Final testing of the proposed system can also differentiate the temperature differences in each zone.